E(im)migrations and displacements: keys, constants and approaches from comparatism (El Hilo de la Fabula, 2023)
This work aims to raise some constants and keys that allow us to address the phenomenon of “e(im)migration” from comparatism. From the understanding of displacement in its polyhedral conformation due to the multiplicity of subjects, voices, spaces, times, languages, memories, identities and movements, the comparative study of “e(im)migration” is proposed in a complex and intertwined inquiry about the myths, archetypes and genotexts that “narrate” and represent the problems and emotions; identity images from imagology; the hodoporic conformation of speech and writing; intercultural and linguistic contacts. These reading keys are outlined as a proposal to address literary productions belonging to the geographical-cultural spaces of Italy and Argentina.
Keywords: E(im)migration; Comparatism; Genotexts; Imagology; Hodoporic writing; Intercultural and linguistic contacts